2009
DOI: 10.1086/596544
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for InvasiveStreptococcus pneumoniaeDisease among Hospitalized Children in Bangladesh: Antimicrobial Susceptibility and Serotype Distribution

Abstract: High levels of nonsusceptibility to cotrimoxazole and susceptibility to penicillin suggest that penicillin may be a drug of choice for treatment of invasive pneumococcal disease. Although serotype distribution is diverse, with changes over time and differences between syndromes observed, implementation of use of the currently available 10- or 13-valent vaccines would have a substantial impact on pneumococcal disease in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…Other studies in asia have yielded mixed rates of antibiotic resistance, possibly influenced by local prescribing patterns. 5,10,13,[22][23][24][25] importantly, isolation of S. pneumoniae in this study may have been limited by the observed *Results from years 1 and 2 were annualized. The number of cases was the total of the number of cases captured during years 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in asia have yielded mixed rates of antibiotic resistance, possibly influenced by local prescribing patterns. 5,10,13,[22][23][24][25] importantly, isolation of S. pneumoniae in this study may have been limited by the observed *Results from years 1 and 2 were annualized. The number of cases was the total of the number of cases captured during years 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate the need for the development of immunization programs, especially in poor countries, to reduce morbidity and mortality (273). Surveillance studies of serotypes causing invasive pneumococcal disease in developing countries have also demonstrated that the current 7-valent pneumococcal vaccine would not cover all serotypes causing invasive disease and have suggested that wider coverage would be provided by the 10-valent or 13-valent pneumococcal conjugate vaccines (13,17,22,98,173,221,267,273,283,307,351,354). The introduction of these vaccines into these vulnerable populations is a crucial, but expensive, step to control this serious infection.…”
Section: Streptococcus Pneumoniaementioning
confidence: 98%
“…According to recent data from the United States in 2007, 93.2% of penicillin-nonsusceptible isolates which caused invasive diseases showed non-PCV7 serotypes, and serotype 19A accounted for 53.2% of these penicillin-nonsusceptible isolates (5). However, since the introduction of PCV7 to Asian countries, the epidemiology of S. pneumoniae in Asian countries has not been well investigated (21,26). Therefore, the ANSORP Study Group performed a prospective, multinational, hospitalbased surveillance study in patients with pneumococcal infections in 11 Asian countries during 2008 to 2009 to investigate the current status of antimicrobial resistance and serotype distribution in S. pneumoniae after the introduction of PCV7.…”
mentioning
confidence: 99%